A comparison of first-, second- and third-cut timothy silages in the diets of finishing beef bulls - Huuskonen, Arto Kalevi; Pesonen, Maiju (Agricultural and Food Science, 2017)
The objective of the present experiment was to study the effects of the third-cut grass silage compared with the first- and second-cut silages on intake, performance and carcass characteristics of finishing bulls. A feeding experiment comprised 45 Simmental bulls which were fed a total mixed ration ad libitum. The three dietary treatments included either first-, second- or third-cut grass silage (550 g kg-1 dry matter), rolled barley (435 g kg-1 dry matter) and a mineral-vitamin mixture (15 g kg-1 dry matter). Dry matter and energy intakes and growth rates of the bulls increased when either first- or third-cut silages were used instead of the second-cut silage. This was probably due to differences in digestibility, which was the lowest in the second-cut silage. There were no differences in intake or growth between the first- and third-cut silage-based rations. No significant differences in carcass traits among the feeding treatments were observed.